Thyroid check-up of people over 18 living with Human Immunodeficiency Virus (HIV), malnourished followed at Notre Dame des Apôtres Hospital in Sarh / Chad - Behanzin, Justin G.; Soudonou, Odile; SOGAN, Clarisse; Agbo, Evrard; Sezan, Alphonse (European Scientific Journal, ESJ, 2022)
Malnutrition and Human Immunodeficiency Virus/Acquire Immunodeciency Syndrome (HIV/AIDS) are public health problems. HIV/AIDS continues to have severe consequences for the nutrition, food security, and other socioeconomic aspects of HIV-infected individuals. The objective of our study is to evaluate the correlation between HIV infection, malnutrition, and thyroid disorders in malnourished people living with HIV/AIDS followed at Notre Dame des Apôtres Hospital in Sarh/Chad. The study included 36 malnourished people living with HIV/AIDS over 18 years of age, followed at the People Living with Human Immunodeficiency Virus (PLWHIV) ward. Our study population consisted of females with 75 percent of cases with a sex ratio (M/F) of 0.33. The most represented age group was between 32 and 59 years. We performed a thyroid assessment of each patient by measuring biochemical parameters such as Thyroid Stimulating Hormone (TSH), Tri-iodothyronin (T3) and Tetra-iodothyronin (T4). The results obtained showed 61.76 percent of thyroid dysfunction prevalence with 11.76 percent primary hypothyroidism, 2.94 percent subclinical hypothyroidism, 5.88 percent TSH-mediated hyperthyroidism, and 41.18 percent central hypothyroidism. As a result, the cases of thyroid dysfunction were high noticed in the age group between 32 and 45 years. Furthermore, the assessment showed that 67 percent of the cases were women. From these results, we can conclude that the combination of the two conditions, malnutrition and HIV infection, weakens the immune system, thus giving way to other opportunistic diseases.